CAFs-released exosomal CREB1 promotes cell progression and immune evasion in thyroid cancer via the positive regulation of CCL20 - Zheng, Chen; Hei, Hu; Zhai, Yifei; Gong, Wenbo; Zhang, Runfang; Zhang, Songtao (Autoimmunity (Chur, Switzerland), 2025)
Exosomes derived from cancer-associated fibroblasts (CAFs) can affect tumor microenvironment (TME) of thyroid cancer (TC). The cAMP response element binding protein 1 (CREB1) acts as a transcription factor to participate in cancer development. Currently, we aimed to explore the molecular mechanism of exosome-associated CREB1 and C-C motif chemokine ligand 20 (CCL20) in TC. The mRNA and protein levels were examined RT-qPCR and western blot. Gene interaction was analyzed using ChIP and dual-luciferase reporter assays. Cell migration, invasion and proliferation were assessed by wound healing, transwell and EdU assays. Exosomes were characterized by morphology observation and western blot. The proliferation and apoptosis of CD8 T cells were detected by immunofluorescence and flow cytometry. assays were performed by establishing xenograft models. CREB1 was highly expressed in TC. CREB1 positively interacted with CCL20 in TC. CREB1 facilitated TC cell migration, invasion and proliferation targeting CCL20. CCL20 expression was reduced by transferring CAFs-secreted exosomes sheltering CREB1 downregulation. Exosomal CREB1 knockdown receded cell progression and enhanced CD8 T function by mediating CCL20. CAFs-associated exosomal CREB1 downregulation inhibited tumorigenesis through affecting CCL20. CAFs-derived exosomes accelerated the malignant behaviors and immune evasion in TC by carrying CREB1 to up-regulate CCL20.